The Holy Spirit and Jesus' Identity: An Analysis Within The Context of The Gospel of John - Adrianus Musu Sili (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
This research wants to know the identity of The Holy Spirit and of Jesus Christ in the gospel of John. Research employs library search that uses some passage relevant to the topic. There are three passage that tell identity of Jesus Christ and Holy Spirit: baptism of Jesus by John in the Jordan river (John 1: 32-34); The Testimony of John the Baptist concerning the Spirit and water (1: 22-24); and Jesus gives the Holy Spirit to disciples (John 20: 22). From these passage, the identity of Jesus Christ and Holy Spirit be formed: identity of Jesus as Messiah and Son of God and Holy Spirit continue the act of Jesus. The audience can provides new insights about the identity of Holy Spirit and Jesus Christ.